PENGEMBANGAN MODEL PEMBELAJARAN BAHASA ARAB BERBASIS TEORI KONSTRUKTIVISME DI PERGURUAN TINGGI - Nasution, Sahkholid; Zulheddi, Zulheddi (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2018)
This study aimed to: 1) describe the conditions of Arabic learning in the State Islamic university of North Sumatra (UIN SU) Medan; 2) develop the Arabic language learning model based on constructivism theory; and 3) know the level of validation of the Arabic language learning model based on constructivism theory. This research applied Research and Development (R D) method with Four Ds model consisting of: define, design, development and dissemination. The results showed (1) the Arabic learning at UIN SU Medan needed much improvement because 48.32% of Arabic language lecturers still used a learning approach not encouraging students to learn actively, collaboratively, and confidently. In other words, the learning process was still teacher-centered. (2) The product (Arabic Language Learning Model) produced was an Arabic learning tool characterized by constructivism, which includes: Syllabus, RPS and Assessment. (3) Constructivism learning and Arabic learning experts assessed the products with an average value of 3.37 (very good).